Impact of sustainable design on India's smart cities development. (2021) - Akhtar, Iram; Kirmani, Sheeraz
Abstract: Smart city is an idea that helps people to use technology for the development of city. Smart cities are developing fast and they present new services which extremely influences planning and policy making, although they take place with urban services. Energy schemes for smart cities development need the higher part of renewable energy sources i.e. solar and wind for electricity and high standard of integration of utilities and industry providing business and households. It is more important to know the renewable energy contribution in the overall smart city's development and planning. This paper highlights and measures the impact of energy planning and smart city interrelation and recognizes the meeting ideas. The energy planning scopes are drawn from the Indian government policy and they are related with smart city's planning environment.